Signature based on RNA-binding protein-related genes for predicting prognosis and guiding therapy in non-small cell lung cancer - Miao, Ti-Wei; Chen, Fang-Ying; Du, Long-Yi; Xiao, Wei; Fu, Juan-Juan (Frontiers in Genetics, 2022)
Background: Studies have reported that RNA-binding proteins (RBPs) are dysregulated in multiple cancers and are correlated with progression and prognosis of disease. However, the functions of RBPs in non-small cell lung cancer (NSCLC) remain unclear. The present study aimed to explore the function of RBPs in NSCLC and their prognostic and therapeutic value. Methods: The mRNA expression profiles, DNA methylation data, gene mutation data, copy number variation data, and corresponding clinical information of NSCLC were downloaded from The Cancer Genome Atlas, Gene Expression Omnibus, and University of California Santa Cruz Xena databases. The differentially expressed RBPs were identified between tumor and control tissues, and the expression and prognostic value of these RBPs were systemically investigated by bioinformatics analysis. Quantitative polymerase chain reaction (qPCR) was performed to validate the dysregulated genes in the prognostic signature. Results: A prognostic RBP-related signature was successfully constructed based on eight RBPs represented as a risk score using least absolute shrinkage and selection operator (LASSO) regression analysis. The high-risk group had a worse overall survival (OS) probability compared to the low-risk group with 1-, 3-, and 5-year area under the receiver operator characteristic curve values of 0.671, 0.638, and 0.637, respectively. The risk score was associated with stage of disease and was an independent prognostic factor for NSCLC when adjusted for age and UICC stage. The constructed nomogram showed a good predictive value. The P53, focal adhesion, and NOD-like receptor signaling pathways were the primary pathways in the high-risk group. The high-risk group was correlated with increased immune infiltration, upregulated relative expression levels of programmed cell death 1 (PD1), and cytotoxic T-lymphocyte associated protein 4 (CTLA4), higher gene mutation frequency, higher tumor mutation burden, and better chemotherapy response. The signature was successfully validated using the GSE26939, GSE31210, GSE30219, and GSE157009 datasets. Dysregulation of these genes in patients with NSCLC was confirmed using qPCR in an independent cohort. Conclusions: An RBP-related signature was successfully constructed to predict prognosis in NSCLC, functioning as a reference for individualized therapy, including immunotherapy and chemotherapy.